2006
DOI: 10.1159/000097446
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Apnea and Bradycardia of Prematurity – Implications for Neurodevelopment

Abstract: Background: Apnea and bradycardia of prematurity (ABP) are possible risks towards damage of the developing brain. Objectives: To characterize the influence of neonatal factors on ABP and to determine the relationship of ABP to neurodevelopmental outcome. Methods: ABP was described in very low birth weight infants (n = 83) using the frequency and severity of ABP episodes with a clinical score considering heart rate, oxygenation, duration and interventions performed during each episode. Neonatal factors were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 33 publications
1
106
0
Order By: Relevance
“…Despite these limitations, available data suggest a link between the number of days of apnea plus the number of days of assisted ventilation, and impaired neurodevelopmental outcome [40] . A relationship has also been shown between delay in resolution of apnea and bradycardia beyond 36 weeks' corrected age and a higher incidence of unfavorable neurodevelopmental outcome [4] . Future studies might better focus on the incidence and severity of desaturation events, as the technical ability to do this is now available, and it is likely that recurrent hypoxia is the detrimental feature of the immature respiratory control exhibited by preterm infants.…”
Section: Neurodevelopmental Outcomementioning
confidence: 96%
See 1 more Smart Citation
“…Despite these limitations, available data suggest a link between the number of days of apnea plus the number of days of assisted ventilation, and impaired neurodevelopmental outcome [40] . A relationship has also been shown between delay in resolution of apnea and bradycardia beyond 36 weeks' corrected age and a higher incidence of unfavorable neurodevelopmental outcome [4] . Future studies might better focus on the incidence and severity of desaturation events, as the technical ability to do this is now available, and it is likely that recurrent hypoxia is the detrimental feature of the immature respiratory control exhibited by preterm infants.…”
Section: Neurodevelopmental Outcomementioning
confidence: 96%
“…Several studies have shown that excessive or persistent apnea and bradycardia are associated with longer-term neurodevelopmental problems [4] . However, a causal relationship is hard to document and the role of accompanying desaturation is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, hypopneic and obstructive apneic episodes are usually suspected only when bradycardia and hypoxemia are present, and the infants are already in severe distress or faint (7,(12)(13)(14)17,29). Repeated occurrences of hypoxemic episodes have been associated with impaired neurodevelopment, including mental retardation, cerebral palsy, blindness, growth retardation, and severe learning difficulties (4,15,17,30,31). Thus, timely detection and characterization of hypopneic and apneic episodes is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent episodes of apnea has significant impact on the blood flow to the vital organs including cerebral ischemia leading to undesired long term poor neuro developmental outcomes such as spastic diplagia. 2,3,4 The prolonged episode of apnea may sometimes require vigorous resuscitation due to fall of blood pressure during the episode and may lead to respiratory failure and death. The evidence is increasing that neonatal apnea is not only associated with brain damage but it may indeed reflect early disturbance of respiratory control system which may predispose infants to SIDS 5. Therefore aggressive approach in prevention and its management which includes specific therapy for the predisposing factors (such as hypoxia, hypothermia, hypoglycemia, infection and gastroesophageal reflux), tactile stimulation and noninvasive respiratory therapy has become increasingly important to stimulate the respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Methylxanthines, such as caffeine, and aminophylline are the mainstay pharmacological treatment for apnea and have proven to reduce chronic lung disease and long-term outcome. 6,7 Doxapram was also used to treat neonates with persistent idiopathic apnea of prematurity unresponsive to methyl xanthenes therapy 8, 9. It is a good respiratory stimulant and increases breathing by stimulating both central and peripheral chemoreceptors 10,11. A number of observational trials have proved the efficacy of the individual drug in the successful reduction of the recurrent apnea and their short term and long term side effects. Here we have compared the efficacy, safety & short term outcomes of aminophylline mono therapy and in combination with doxapram in unresponsive neonatal apnea.…”
Section: Introductionmentioning
confidence: 99%